Uncovering the potential of biofabricated Ananas comosus peel selenium nanoparticles for antibacterial, antibiofilm, suppression of virulence genes (can and LuxS), anticancer, and antioxidant properties - Mohamed K. Y. Soliman; Salem S. Salem (BMC Biotechnology)
Abstract This research employed Ananas comosus (pineapple) peel waste (PPW) extract for producing selenium nanoparticles (SeNPs) using an ecologically feasible way, aimed at various medical uses. Our analysis demonstrated that the PPWextract was a significant supplier of several important phytochemicals. The synthesized SeNPs were comprehensively characterized via XRD, FTIR, SEM, EDX, UV-Vis, and HRTEM which exhibiting a spherical shape with dimensions between 33 and 73 nm. Additional experimental assessments of SeNPs were carried out to ascertain their suitability for usage in biology applications. The findings suggest that obtained SeNPs may effectively combat multiple bacteria, including S. aureus, E. coli, B. subtilis, E. faecalis, and K. pneumonia. Additionally, SeNPs exhibited antibiofilm capacity for both MRSA and E. coli with inhibition reported to be 64.8% and 54.4% at 100 µg/mL respectively. In the range of 62.5–31.25 µg/mL SeNPs reduced expression of two essential genes required for S. aureus to generate biofilms, cna (0.9 fold change), and quorum sensing gene LuxS of E. coli (4.2 folds of control to 3.4 folds of treated) in comparison to the RecA gene. The antioxidant capacity of SeNPs reported an IC50 value of 98.3 µg/mL. The formed SeNPs demonstrated anticancer efficacy in combating the HepG2 malignant cell line, with an IC50 value of 113.02 µg/mL.